A CRITICAL STUDY IN THE COMPLEX-POLYMORPHOUS GENUS SCHIMA (THEACEAE) - BLOEMBERGEN, S. (REINWARDTIA, 1952)
Â 1. The author considers the genus Schima monotypic. Its only species, Schima wallichii (DC.) Korth., is subdivided into nine geographically separated subspecies and three varieties.These may be recognised sometimes by one dominating chax*acter,mostly, however, by a complex of characters.Several new combinations are made.2. Yet the variability of most of the subspecies is still often enormous and at first sight appears complex. Thus we may often encounter the polymorphy of the whole species in its subspecies again. It was the striking different percentage-numbers of(phenotypically) about the same characters which turned the scale in favour of the recognition of the subspecies, besides their geographic separation.The attempts made by the author to divide certain resulting complex-polymorphous subspecies into units of still lower rank and to trace correlations with peculiarities of environment such as different heights above sealevel, or with different stages in the age of the trees, failed. 3. On account of these negative results and the above mentioned different percentage-numbers for phenotypically about the same characters, the author came to the conclusion that the most probable explanation is that the variability within the subspecies is just due to Mendel-segregation and nothing else.It looks very much as if one is dealing here with the inheriting of striking characters, each caused by one or only a few polymeric factors, characters which hold their own, just as in panmictlcally propagated populations (by cross-pollination). This explanation, too,makes the striking fact that in some subspecies we find back phenotypically the whole, or part, of the polymorphy of the entire species more understandable, as well as the fact that individuals of different subspecies may agree phenotypically, whereas genotypically they belong to different races (subspecies), Moreover, all these phenomena strongly support the monotypic conception of the genus. 4. The author saw few examples from the area outside Indonesia. However,this does neither influence his monotypic conception of the genus, nor his method of dividing it into units of lower ranks. The study of the scanty amount of specimens,literature, and the drawings seen appeared more than sufficiently convincing. Yet he is not quite certain whether the correct rank was ascribed to some of the lower taxa involved. It would perhaps have been advisable to consider the variety superba and the continental parts of the subspecies oblata and monticola as distinct subspecies.Future consideration of this matter shall have to decide.